COVID-19 surveillance in wastewater: An epidemiological tool for the monitoring of SARS-CoV-2 - Maryam, Sajida; Ul Haq, Ihtisham; Yahya, Galal; Ul Haq, Mehboob; Algammal, Abdelazeem M.; Saber, Sameh; Cavalu, Simona (Frontiers in Cellular and Infection Microbiology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has prompted a lot of questions globally regarding the range of information about the virus’s possible routes of transmission, diagnostics, and therapeutic tools. Worldwide studies have pointed out the importance of monitoring and early surveillance techniques based on the identification of viral RNA in wastewater. These studies indicated the presence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in human feces, which is shed via excreta including mucus, feces, saliva, and sputum. Subsequently, they get dumped into wastewater, and their presence in wastewater provides a possibility of using it as a tool to help prevent and eradicate the virus. Its monitoring is still done in many regions worldwide and serves as an early “warning signal”; however, a lot of limitations of wastewater surveillance have also been identified.